Influences of 'appscape' on mobile app adoption and m-loyalty. (November 2018) - Kumar, Deepak S.; Purani, Keyoor; Viswanathan, Shyam A.
Abstract: Influence of visual aesthetics in product design, service environments and websites are well explored but increasing usage of mobile interfaces and the different use context demand investigation of influence of visual aesthetics of mobile app interfaces – 'appscapes' on mobile app adoption and m-loyalty. In this study, the conceptual model is developed by applying Kaplan's information processing model from environmental psychology and integrating it into the Technology Acceptance Model, thereby linking visual aesthetics of mobile apps to m-loyalty. The responses ( n = 308 ) are collected using field experiments using four existing apps as stimuli. Results of PLS structural equation modelling reveal positive linkages between holistic visual aesthetic dimensions and outcomes of m-loyalty. Theoretical and managerial implications are discussed.